Panel Summary: Improving Care and Support to Unpaid Caregivers in Ontario - Gauvin, François-Pierre (My University, 2014)
A summary of what was learned from a citizen panel that addressed problems related to unpaid caregivers, options for addressing these problems, key implementation considerations, and next steps for improving care and support for unpaid caregivers in Ontario.
Keywords: caregivers; Canada